Multigenerational Financial Support (Nafkah) Practices in the Division of Economic Responsibilities Between Husband and Wife (A Study in the Subdistrict of Tanete Riattang Barat) - Hafilah Ramadani; Lukman Arake; Hamzah Hamzah (STAI Miftahul Ula Nganjuk, 2026)
This study analyzes the distribution of economic responsibilities within multigenerational Bugis families in the West Tanete Riattang District from the perspective of Islamic law. The research employed a qualitative field method with a normative theological and sociological approach, utilizing observation, interviews, and documentation. The findings reveal four patterns of economic distribution: collective, separate households, supported by parents, and supported by children. Conflicts that arise regarding privacy, parenting styles, customs, and the division of roles are resolved through communication and deliberation. Under Islamic law, the husband remains the primary provider, while the involvement of other family members is voluntary and may be accepted as ‘urf ṣaḥīḥ as long as it does not contradict sharia. Based on the maqāṣid syarī‘ah, this practice is valid if it maintains a balance between the nuclear family, filial piety toward parents, and domestic harmony.